Aortic aneurysm morphology for planning endovascular procedures. - White, R A (1997)
Endovascular prosthesis repair of abdominal aortic aneurysms is based upon the development of low-profile devices that can be expediently deployed within the aneurysm, excluding it from intraluminal pressure. Many factors affect the treatment of patients in this manner, including the morphology of the proximal and distal fixation sites, the diameter and disease state of the access vessels, and the ability of the device to conform to the many anatomic variations of aneurysms. In addition, preliminary data suggest there is progressive shrinkage and morphologic change in the configuration of an aneurysm following exclusion, which not only affects the alignment of the device but may also influence its healing and stability. This paper reviews the morphologic parameters of aneurysms relevant to endovascular repair and describes the imaging technologies used to assess these parameters before, during, and after intervention.